2017
DOI: 10.1016/j.cell.2017.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Replication-Transcription Conflicts Generate R-Loops that Orchestrate Bacterial Stress Survival and Pathogenesis

Abstract: SUMMARY Replication-transcription collisions shape genomes, influence evolution, and promote genetic diseases. Although unclear why, head-on transcription (lagging strand genes) is especially disruptive to replication and promotes genomic instability. Here, we find that head-on collisions promote R-loop formation in Bacillus subtilis. We show that pervasive R-loop formation at head-on collision regions completely blocks replication, elevates mutagenesis, and inhibits gene expression. Accordingly, the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
306
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(327 citation statements)
references
References 68 publications
(101 reference statements)
20
306
1
Order By: Relevance
“…We detected R loops regardless of transcriptionreplication orientation, but when Yra1 is overexpressed, an R-loop-dependent increase in recombination occurred in both systems, whether head-on or codirectional, demonstrating that they are present in both situations. Therefore, our data indicate that R loops are formed cotranscriptionally regardless of replication and may be present before the replication fork arrives; that is, it is not the transcription-replication collisions the cause of the R loops (Bermejo et al 2011;Hamperl et al 2017;Lang et al 2017). Consistently, R loops are also observed in the codirectional orientation in a bacterial chromosome too (Lang et al 2017) and are detected in G1 cells in yeast and human cells (Castellano-Pozo et al 2012;Bhatia et al 2014).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…We detected R loops regardless of transcriptionreplication orientation, but when Yra1 is overexpressed, an R-loop-dependent increase in recombination occurred in both systems, whether head-on or codirectional, demonstrating that they are present in both situations. Therefore, our data indicate that R loops are formed cotranscriptionally regardless of replication and may be present before the replication fork arrives; that is, it is not the transcription-replication collisions the cause of the R loops (Bermejo et al 2011;Hamperl et al 2017;Lang et al 2017). Consistently, R loops are also observed in the codirectional orientation in a bacterial chromosome too (Lang et al 2017) and are detected in G1 cells in yeast and human cells (Castellano-Pozo et al 2012;Bhatia et al 2014).…”
Section: Discussionsupporting
confidence: 67%
“…These results argue that RNA-DNA hybrids are an important source of genome instability in systems undergoing head-on transcription-replication conflicts but not in those undergoing codirectional conflicts. This interpretation would be consistent with the recent observation in human cells using similarly designed plasmid-based constructs in which transcription is driven from a bacterial T7 promoter and replication is driven from an EpsteinBarr virus replication origin (Hamperl et al 2017) as well with R-loop-dependent replication impairment observed in the Bacillus subtillis genome (Lang et al 2017). However, none of these results provide any answer to whether R loops are formed only in head-on transcription-replication or after replication.…”
Section: R-loop-mediated Genome Instability Is Linked To Head-on Transupporting
confidence: 46%
See 2 more Smart Citations
“…A single RNAP moving head-on can dislodge the replisome in vitro (26, 50). In vivo, in a head-on collision, the replisome disassembles, the DNA breaks, and local mutation rates more than double (7, 14, 24, 28, 38, 39, 41, 48, 55, 65). Therefore, despite the common assumption in the field, the consequences of head-on conflicts are not necessarily linked to transcription levels.…”
Section: Introductionmentioning
confidence: 99%